Research of visual attention in basketball shooting: A systematic review with meta-analysis - Sirnik, M.; Erculj, F.; Rošker, J. (International Journal of Sports Science & Coaching, 2022)
Visual attention has a significant impact on shooting performance in basketball. Over the past 35 years, researchers have explored individual concepts of visual attention, such as gaze fixation, the number and direction of saccades, and their effects on shooting accuracy. The last gaze fixation, also known as the quiet eye, was found to be particularly important. The aim of this paper was therefore to systematically review the literature to present how visual attention and the quiet eye contribute to shooting performance and how they are affected by anxiety, training, defensive pressure, and fatigue. The 26 articles selected were divided into two categories; the first category included studies that examined visual attention during free throws, and the second category included studies examining jump shots. In addition, we performed a meta-analytic comparison to determine whether the duration of the quiet eye differs with respect to temporal constraints. Results show that for both jump shots with or without defence and free throws, a longer quiet eye durations and a lower number of gaze fixations are associated with better performance. For a successful shot, the quiet eye phase must occur at the right moment, which is likely due to visuomotor reaction latency prior to elbow extension. Furthermore, improvement in shooting performance can be achieved through quiet eye training or traditional training. Nevertheless, individual factors such as quiet eye timing, systematic training, and visual attention in top basketball players of different playing positions need to be further explored as this will provide even more information for individual`s improvement.